TREND ANALYSIS AND DATA MODELING OF DOMESTIC WASTEWATER QUALITY AS PREPARATION TOWARDS SMART ENVIRONMENT PLATFORM DEVELOPMENT - Helmy Faisal Muttaqin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In achieving the vision towards Smart City, related to the management of industrial sector, especially small and medium enterprises (MSMEs) or home-based businesses that contribute significantly to the economic sector, the management of household wastewater is one of the domains in the Smart Environment that must be a significant concern. River water pollution caused by domestic / home waste disposal and factories must be monitored on an ongoing basis. Sampling for laboratory tests is still used today. It is expected that in the future, wastewater quality testing in the laboratory can be replaced by the use of Internet of Things sensors so that wastewater quality can be monitored directly in real-time. However, the results of laboratory testing that have been collected can still be used to see trends in decreasing or improving water quality, so that they can be used as a reference for developing smart environment platforms shortly.